Reproductive intentions of women in Europe: analysis of the results of sociological research on the program «Generations and gender» - Rotman, David G.; Denisov, Artur Y.; Belov, Andrei A. (Journal of the Belarusian State University. Sociology, 2019)
The article analyzes age features of women’s reproductive intentions for a three-year perspective on the basis of sociological research of the international program «Generations and Gender Programme». The reproductive potential is estimated, that is the level of fertility, provided that all reproductive intentions are fully realized. A comparative analysis of reproductive intentions and reproductive potential in the countries of Europe has been carried out. It was concluded that there is a connection between the actual level of fertility and the prevalence of the norm of large families, as well as between the level of reproductive intentions and actual fertility.
Keywords: reproductive intentions; expected fertility; reproductive behavior; total fertility rate; hypothetical generation; large families